Neoliberal Legality as Dual Process: Embeddedness, Courts and Crime Prevention in the United States - Campeau, Holly; Levi, Ron (British Journal of Criminology, 2019)
This article advances research on 'neoliberal legality' to focus on the role of courts in response to neoliberal crime prevention approaches. Drawing on Karl Polanyi's analysis of embeddedness in market capitalism, along with criminological research on the penal state, we analyse three case studies reflecting central crime prevention approaches of the neoliberal era in the United States. We find that neoliberal legality is more complex than simply legitimating or resisting neoliberal policies. We highlight how courts did both at once—they moderated the harshest edges of neoliberal policies through alternative symbolic frames, yet in so doing also legitimated the core of neoliberal crime prevention efforts. We argue that neoliberal legality operates through this dual process, in which the basic thrust of neoliberalism is legitimated by also having policies moderated, recast and embedded within other social and juridical expectations.
Criminology; Sociolegal Studies
Keywords: POLANYI; Karl; 1886-1964; United States; capitalism; courts; crime prevention; embeddedness (socioeconomic theory); law; neoliberal legality; neoliberalism; penal state

The Big Picture: 2010 Presidential Address to the American Society of Criminology* - Rosenfeld, Richard (Criminology, 2011)
Microanalysis holds sway over macroanalysis in contemporary criminology. All of criminology would be better off if greater attention were devoted to the big picture—the relationship between crime and the interplay of institutions in the social systems of whole societies. Microlevel researchers often assume that the reduction of individual criminal propensities leads ipso facto to reductions in aggregate crime rates, but the implied connection is illusive, has not been demonstrated, and is belied by the macroanalysis of crime. The perspectives, methods, and data of macrocriminology also need to be developed, however, if they are to advance our understanding of crime at the level of social systems. Emile Durkheim, Talcott Parsons, Karl Polanyi, and C. Wright Mills have contributed essential building blocks for the study of the big picture of crime. Improvements in the quality and timeliness of aggregate crime data, finally, are necessary to bolster the policy relevance of macrocriminology.
Criminology
Keywords: MILLS; C. Wright; PARSONS; Talcott; aggregate crime rates; macrocriminology; social institutions

Anomie, Social Change and Crime - Bernburg, Jon Gunnar (British Journal of Criminology, 2002)
The last decade has seen a revived interest in using anomie theory in crime and deviance research. The present paper contributes to this development by offering an examination of a particular extension of anomie theory, namely, Messner and Rosenfeld's Institutional-Anomie theory. Explicating Institutional-Anomie theory relative to the sociologies of Durkheim, Merton and Polanyi, I find that this theory goes beyond Merton by using a strain of thought that is critical of liberal society. By bringing in the notion of the disembedded market economy, a central notion in the institutionalism of Polanyi and Durkheim, this theory links crime, anomie, and contemporary social change. I also discuss some of the limitations of linking crime with societal level processes in a Durkheimian rather than Mertonian manner.
Sociology; Criminology
Keywords: DURKHEIM; Emile; MERTON; Robert; anomie; crime; criminology; disembeddedness